2019
DOI: 10.33603/jibm.v3i1.2093
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Profitabilitas Bank Perkreditan Rakyat (BPR) di Provinsi Jawa Timur

Abstract: The data analysis technique using panel data regression. The results showed that of simultaneously CAR, LDR, BOPO, and NPL have an effect on the ROA. Partially CAR, LDR, and BOPO have a negative effect on ROA, while the NPL variable has no effect on ROA. The implications of this research is that so that the Rural banks determines the appropriate credit distribution ceiling based on the capital consideration held.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 4 publications
3
20
2
6
Order By: Relevance
“…The higher CAR, the stronger the company's ability to bear credit risk where ROA will be better and can increase company profits. The results of this study are in line with research conducted by Sofyan (2019) whose results indicate that CAR negatively affects ROA. The lower the CAR, the weaker the company's ability to bear credit risk.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The higher CAR, the stronger the company's ability to bear credit risk where ROA will be better and can increase company profits. The results of this study are in line with research conducted by Sofyan (2019) whose results indicate that CAR negatively affects ROA. The lower the CAR, the weaker the company's ability to bear credit risk.…”
Section: Methodssupporting
confidence: 91%
“…In general, the value of a company's profitability can be used as an indicator to measure the performance of a company. Profitability in this study was measured using Return On Assets (ROA) (Sofyan, 2019). The profitability ratio also plays an important role in the company's financial position.…”
Section: Introductionmentioning
confidence: 99%
“…A larger NPL value reflects an increase in non-performing loans that is borne by a RURAL BANK. The results of the study are in accordance with Berliana [17] and Taqiyya [15] which show non-performing loans can cause Rural Banks to lose their main income which comes from loan interest income. This research is different from the findings of Sofyan [18] that obtaining NPL does not have a significant effect on ROA because losses due to bad credit are borne by the capital owned by the bank.…”
Section: The Effect Of Npl On Roasupporting
confidence: 87%
“…Bank Indonesia Regulation Number 15/2/PBI/2013 states that a bank that has an NPL of more than 5 percent of total credit can endanger its business continuity [16]. Berliana [17] shows that the increased NPL value reflects the increasing number of non-performing loans that cannot be a profit for Rural Bank. Unlike Berliana [17], Sofyan's research [18] found that NPLs do not have a significant effect on ROA because losses due to non-performing loans can be borne by bank capital.…”
Section: Figure 1 Credit and Deposits Conventional Rural Banks In Indonesia For 2015-2019mentioning
confidence: 99%
“…The same is true for the banks, but for banks, in addition to increasing the company value, the banks have other interests by merging. The Bank's interest is to increase its capital, because banks are required to meet the capital adequacy ratio (CAR) set by Bank Indonesia (Sofyan, 2019).…”
Section: Introductionmentioning
confidence: 99%